Impact of the post-thermal annealing on OFETs using printed contacts, printed organic gate insulator and evaporated C60 active layer. (December 2018) - Tao, Zhi; Mohammed-Brahim, Tayeb; Lei, Wei; Harnois, Maxime; Jacques, Emmanuel
Highlights: Investigation of thermal annealing process influence on printed n-type OFET. Investigation of organic semiconductor layer thickness impacts on C60 OFET. Investigation on relationships between OFET stability and C60 crystalline structure. Investigation on Pseudo-CMOS inverter logic circuits. Abstract: Towards fully printed organic electronics, bottom-gate, bottom contacts fullerene based organic FETs (OFETs) are fabricated using inkjet printing drop-on-demand technology for the deposition of gate contact, organic gate insulator and source and drain contacts. The last layer of this structure that is the semiconducting fullerene C60 film is deposited by thermal evaporation at ambient temperature. Using physical and electrical analysis, the electrical performances are optimized by studying the effect of the thickness of the C60 film and of the post-thermal annealing of the OFET. A quantitative relationship between the crystalline structure of the C60 semiconducting layer (grain size and surface roughness) and the electrical performance of the OFETs is demonstrated. The best performance as determined from the values of the electrical parameters of the OFETs is obtained for 90 nm thick C60 film and after an annealing of the OFET at 200 °C. The answer of present nearly fully printed OFETs to a voltage pulse applied to the gate leads to a switching time of 13 ms, and then to application frequency of some 10 Hz. This result opens the way to potential main application in electronic circuits for the treatment of analog signals coming from the human body activities.